2009
DOI: 10.1080/02699930902985894
|View full text |Cite
|
Sign up to set email alerts
|

Variety is the spice of life: A psychological construction approach to understanding variability in emotion

Abstract: There is remarkable variety in emotional life. Not all mental states referred to by the same word (e.g., “fear”) look alike, feel alike, or have the same neurophysiological signature. Variability has been observed within individuals over time, across individuals from the same culture, and of course across cultures. In this paper, I outline an approach to understanding the richness and diversity of emotional life. This model, called the conceptual act model, is not only well suited to explaining individual diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
236
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 117 publications
15
236
0
7
Order By: Relevance
“…It consists of continuous cycles of bodily responses, changes in representations of body states, consciousness of feelings likely to trigger new embodied responses and so on. Experimental psychologists Barrett (2009) and Russell (2003) equally suggest a contingent, plastic and flexible, constructive feedback process, as core affects (core embodied, psycho-physiological states) are simultaneously perceived, organized, categorized, labelled and communicated becoming socially recognizable 'emotions'. Any initial bodily hit, in other words, is always already occurring within an ongoing stream of meaning-making or semiosis.…”
Section: Affect and Discourse -The Emergence Of An Impassementioning
confidence: 99%
“…It consists of continuous cycles of bodily responses, changes in representations of body states, consciousness of feelings likely to trigger new embodied responses and so on. Experimental psychologists Barrett (2009) and Russell (2003) equally suggest a contingent, plastic and flexible, constructive feedback process, as core affects (core embodied, psycho-physiological states) are simultaneously perceived, organized, categorized, labelled and communicated becoming socially recognizable 'emotions'. Any initial bodily hit, in other words, is always already occurring within an ongoing stream of meaning-making or semiosis.…”
Section: Affect and Discourse -The Emergence Of An Impassementioning
confidence: 99%
“…Finding that they were more consistent than nonmusicians in using structural cues to respond accords well with this hypothesis. Barrett and colleagues (Barrett, 2006(Barrett, , 2009Lindquist & Barrett, 2010) have suggested that individual differences in emotional responses and experience might reflect differences in the granularity of emotion concepts, which could be trained. According to this theoretical framework, individuals with higher emotional granularity are more precise, specific, and differentiated in categorizing affective states, while those with low granularity experience and describe emotions in a more global and less differentiated way.…”
Section: Musical Expertise and Emotion Recognition In Musicmentioning
confidence: 99%
“…Social emotions, which from the outset were constructed by cultural traditions, became more varied and context-dependent. For modern humans, E. F. Barrett and her colleagues have convincingly argued that even emotion-words such as 'afraid' or 'angry' act as 'place holders', categorizing and crystallizing the fuzzy feelings associated with particular behaviours [63][64][65].…”
Section: How Language Changed Human Emotionsmentioning
confidence: 99%